Dragon kingdom of Wrenly. Book 1, The coldfire curse - Quinn, Jordan (Quinn, Jordan. Dragon Kingdom of Wrenly., 2021)
"Ruskin, the pet dragon of the royal family of Wrenly, forms new friendships with the dragons of Crestwood and goes on exciting adventures"--